Unraveling the complexity of Disorders of the Gut-Brain Interaction: the gut microbiota connection in children - Rosa, Dimas; Zablah, Roberto Arturo; Vazquez-Frias, Rodrigo (Frontiers in Pediatrics, 2024)
Disorders of Gut-Brain Interaction (DGBIs)," formerly referred to as "Functional Gastrointestinal Disorders (FGIDs)," encompass a prevalent array of chronic or recurring gastrointestinal symptoms that notably impact the quality of life for affected children and their families. Recent studies have elucidated the intricate pathophysiology of DGBIs, underscoring their correlation with gut microbiota. This review seeks to explore the present comprehension of the gut microbiota's role in DGBI development. While other factors can contribute to DGBIs, the gut microbiota prominently influences the onset and progression of these conditions. According to the Rome IV diagnostic criteria, DGBI prevalence is approximately 40% worldwide. The Rome Foundation has diligently worked for nearly three decades to refine our comprehension of DGBIs. By centering on the gut microbiota, this review sheds light on potential therapeutic interventions for DGBIs, potentially enhancing the quality of life for pediatric patients and their families.Marco Luis Herrera reviewed the text for any typographical, spelling, or formatting errors. To Marie Claire Arrieta for his constant advice and guidance.